Adsorption of SO2 on pristine and defective single-walled MgO nanotubes: a dispersion-corrected density-functional theory (DFT-D) study. (22nd January 2021) - Wang, Mengxin; Chen, Yingrui; Wang, Wenju; Zhang, Teng
Abstract: The dispersion-corrected density functional theory (DFT-D) has been used to study the interactions of SO2 on the pristine and defective single-walled MgO nanotubes (MgONTs). A geometric optimization was performed for MgONTs and adsorbents/MgONTs. The adsorption energies of SO2 molecules at different layers of MgONTs were considered. The adsorption property of SO2 was analyzed in terms of the adsorption energy, the electron donation (basicity), and the atomic charges on the adsorbed materials. The densities of states (DOS) have been calculated and used for examining the adsorption properties. In addition, the presence of vacancy defects increases the adsorption energies of the SO2 molecules. The band gaps of the defective MgONTs are sensitive to SO2 molecules.